Keanekaragaman Plankton di Sungai Way Umpu, Kabupaten Way Kanan, Provinsi Lampung - Pratiwi, Ratih -; Tugiyono, Tugiyono; Rustiati, Elly Lestari; Handayani, Kusuma (Faculty of Mathtmatics and Natural Sciences, 2022)
Plankton are organisms that live or float in microscopic water and have an important role in aquatic ecosystems. The Way Umpu River is widely used by local residents as a development area in the agricultural, mining, fishery, transportation, industrial, and domestic needs of the community. Research on plankton diversity was carried out in the Way Umpu River, Way Kanan Regency, Lampung Province from August 2021 to February 2022. The purpose of this study was to determine the plankton diversity index and water quality supported by physical and chemical parameters. Sampling used a survey method based on land use at 7 research stations. The results found that there were 22 types of plankton grouped into 10 classes, namely 4 groups of zooplankton, namely Class Rhizopoda, Euglenophyceae, Ciliatea, and Oligotrichea, and 6 groups of phytoplankton namely Class Cyanophyceae, Bacillariophceae, Trebouxiophyceae, Zygnemophyceae, Chlorophyceae, and Fragilariophyceae. The diversity index (H') of all research stations ranged from 1.06 to 1.77. This shows that the diversity of plankton in the Way Umpu River, Way Kanan Regency is classified as moderate and the water conditions are categorized as moderately polluted with a value range of 1<H'<3.